Karmic Cascades: Ranking Content and Conditioning Thought on reddit.com. - Mitchell, Liam (Techné: Research in Philosophy & Technology)
The content ranking system of reddit.com, the English language Internet's most popular social news website, plays a large but often unnoticed role in shaping what users see and how they think. By pairing informational cascade theory with textual analysis, I argue that the "karma" system elevates particular forms of content over others and generates numerical cues that unconsciously guide users' judgments about said content and about the world. By drawing on Heidegger's account of modern technology, I argue that the karma system both symptomatizes and engenders an ontological perspective according to which things in general are taken as available, evaluable, and disposable.